2021
DOI: 10.33073/pjm-2021-043
|View full text |Cite
|
Sign up to set email alerts
|

Can Lactobacillus spp. Be a Factor Reducing the Risk of Miscarriage?

Abstract: Pregnancy loss is a common obstetric problem. Significant causes of miscarriage include genetic and epigenetic disorders of the embryo, immunological and endocrine factors, uterine malformations, improper embryo selection, and lifestyle. Perhaps a hitherto underappreciated cause of miscarriage may be an abnormal microbiota composition of the female reproductive system. Lactobacillus spp. is the most common bacteria within the reproductive tract. However, the protective role of Lactobacilli in the vagina has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 145 publications
(250 reference statements)
0
7
0
Order By: Relevance
“…has been shown to benefit the effects of assisted reproduction and the women with colonized follicular fluid show changes in the immune response and cytokine profile. The authors therefore proposed the identification of microorganisms in the follicle as a diagnostic test of the true cause of infertility and the prediction of a successful assisted reproduction cycle [102,103]. The bacteria of the genera Pseudomonas, Acinetobacter, Vagococcus and Sphingobium in the fallopian tubes and in the follicles is a poor prognostic factor for IVF, and their presence increases the likelihood of bacterial vaginosis in women with tubal infertility [104].…”
Section: The Microbiota Of Female and Male Reproductive Systemmentioning
confidence: 99%
“…has been shown to benefit the effects of assisted reproduction and the women with colonized follicular fluid show changes in the immune response and cytokine profile. The authors therefore proposed the identification of microorganisms in the follicle as a diagnostic test of the true cause of infertility and the prediction of a successful assisted reproduction cycle [102,103]. The bacteria of the genera Pseudomonas, Acinetobacter, Vagococcus and Sphingobium in the fallopian tubes and in the follicles is a poor prognostic factor for IVF, and their presence increases the likelihood of bacterial vaginosis in women with tubal infertility [104].…”
Section: The Microbiota Of Female and Male Reproductive Systemmentioning
confidence: 99%
“…Many studies show that Lactobacillus spp. dominates the vaginal microbiota of healthy women (Ravel et al 2011;Gajer et al 2012;Kiecka et al 2021). Due to Lacto bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The first study on the bacterial composition of the uterus reported that real-time quantitative PCR identified 95% of 58 patients undergoing hysterectomy as having a uterine microbiota, with the most common species being L. iners (in 45%) and Prevotella (in 33%) (Mitchell et al, 2015). Several subsequent studies have found that Lactobacillus is the most prominent genus in the endometrium, with Lactobacillus being identified in both endometrial fluid and endometrial biopsies (Franasiak et al, 2016;Moreno et al, 2016;Miles et al, 2017;Moreno and Simon, 2019;Kiecka et al, 2021). It is unclear whether Lactobacillus is an actual endometrial colonizer or whether it ascended from the vagina.…”
Section: Endometrial Microbiomementioning
confidence: 99%